2010
DOI: 10.1161/circresaha.109.209189
|View full text |Cite
|
Sign up to set email alerts
|

TIMP2 Deficiency Accelerates Adverse Post–Myocardial Infarction Remodeling Because of Enhanced MT1-MMP Activity Despite Lack of MMP2 Activation

Abstract: Rationale: Myocardial infarction (MI) results in remodeling of the myocardium and the extracellular matrix (ECM). Tissue inhibitors of metalloproteinases (TIMPs) are critical regulators of ECM integrity via inhibiting matrix metalloproteinases (MMPs). TIMP2 is highly expressed in the heart and is the only TIMP that, in addition to inhibiting MMPs, is required for cell surface activation of pro-MMP2. Hence, it is difficult to predict the function of TIMP2 as protective (MMP-inhibiting) or harmful (MMP-activatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
141
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 55 publications
13
141
1
1
Order By: Relevance
“…In mouse models, Th2 induction resulted in reduced ventricular stiffness, and Th1 cells were involved in initiation of fibrosis and collagen crosslinking (Yu et al, 2005;, whereasanother 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 study did detecta shift from Th1 to Th2 response in old mice in association with interstitial myocardial fibrosis (Cieslik et al, 2011). We observed a reduction of all three immune modulatory markers (IL-2, IL-4,IFN-γ)with age in thefemale cats, which might be consistent with a generally reduced myocardial inflammatory response, as suggested by thereduced transcriptionof IL-1 and IL-6.Aupperle and co-authors (2011) observed reduced TIMP-2 expression in association with myocardial fibrosis in cats.In older sheep (> 8 years), rat and mouse models, higher myocardial MMP-2 and reduced TIMP-2 mRNA and protein expression, as well as cardiomyocyte hypertrophy and perivascular and interstitial fibrosis, imbalanced cardiac remodelling and impaired repair was observed (Kandalam et al, 2010;Wang et al, 2010;Horn et al, 2012;Givvimani et al, 2013). The age-associated reduced TIMP-2 and MMP-2 transcription in female and male cats, respectively,suggests therefore a pro-fibrotic potential and impaired repair of the female myocardium, and further supports a reactive male myocardium facilitating appropriate repair (Davis et al, 2007;Chen and Frangogiannis, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse models, Th2 induction resulted in reduced ventricular stiffness, and Th1 cells were involved in initiation of fibrosis and collagen crosslinking (Yu et al, 2005;, whereasanother 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 study did detecta shift from Th1 to Th2 response in old mice in association with interstitial myocardial fibrosis (Cieslik et al, 2011). We observed a reduction of all three immune modulatory markers (IL-2, IL-4,IFN-γ)with age in thefemale cats, which might be consistent with a generally reduced myocardial inflammatory response, as suggested by thereduced transcriptionof IL-1 and IL-6.Aupperle and co-authors (2011) observed reduced TIMP-2 expression in association with myocardial fibrosis in cats.In older sheep (> 8 years), rat and mouse models, higher myocardial MMP-2 and reduced TIMP-2 mRNA and protein expression, as well as cardiomyocyte hypertrophy and perivascular and interstitial fibrosis, imbalanced cardiac remodelling and impaired repair was observed (Kandalam et al, 2010;Wang et al, 2010;Horn et al, 2012;Givvimani et al, 2013). The age-associated reduced TIMP-2 and MMP-2 transcription in female and male cats, respectively,suggests therefore a pro-fibrotic potential and impaired repair of the female myocardium, and further supports a reactive male myocardium facilitating appropriate repair (Davis et al, 2007;Chen and Frangogiannis, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase and TIMP imbalance and ECM degradation and deposition are associated withcardiac diseases and dysfunction (Spinale, 2007), but onlylittle is known about their role in age related cardiac changes. Mouse models ofageingexhibit varying MMP, TIMP and transforming growth factor (TGF)-β mRNA and protein production (Brooks and Conrad, 2000;Lindsey et al, 2005;Tian et al, 2007;Kandalam et al, 2010;Wang et al, 2010;Givvimani et al, 2013;Uchinaka et al, 2014). 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 Cytokines play an important role in the activation of MMPs and TIMPs.…”
Section: Increased Ventricular Stiffness Is Caused By Imbalanced Extrmentioning
confidence: 99%
“…Western blotting was performed to detect collagen type I (COL1A1) (Santa Cruz Biotechnology) and ␣-elastin (Abcam Inc.), and in vitro gelatin zymography was carried out as before (30). A Coomassie Bluestained SDS-PAGE gel (after proteins were transferred to PVDF membrane) was used as a loading control.…”
Section: /Mmp2mentioning
confidence: 99%
“…In situ gelatin zymography was performed on 14-m cryosections as described (31). Total collagenase and gelatinase activities were measured using Enzchek collagenase (catalog number D-12060) and elastase (catalog number E-12056) activity assay kits (from Millipore) as before (30). Briefly, 50 g of protein extract was incubated with fluorescently labeled collagen or elastin substrate.…”
Section: /Mmp2mentioning
confidence: 99%
See 1 more Smart Citation